STAT4 deficiency reduces the development of atherosclerosis in mice. Issue 1 (November 2015) - Taghavie-Moghadam, Parésa L.; Gjurich, Breanne N.; Jabeen, Rukhsana; Krishnamurthy, Purna; Kaplan, Mark H.; Dobrian, Anca D.; Nadler, Jerry L.; Galkina, Elena V.
Abstract Atherosclerosis is a chronic inflammatory process that leads to plaque formation in large and medium sized vessels. T helper 1 (Th1) cells constitute the majority of plaque infiltrating pro-atherogenic T cells and are induced via IFNγ-dependent activation of T-box (Tbet) and/or IL-12-dependent activation of signal transducer and activator of transcription 4 (STAT4). We thus aimed to define a role for STAT4 in atherosclerosis. STAT4-deficiency resulted in a ∼71% reduction (p < 0.001) in plaque burden in Stat4−/−Apoe−/− vs Apoe−/− mice fed chow diet and significantly attenuated atherosclerosis (∼31%, p < 0.01) in western diet fed Stat4−/−Apoe−/− mice. Surprisingly, reduced atherogenesis in Stat4−/−Apoe−/− mice was not due to attenuated IFNγ production in vivo by Th1 cells, suggesting an at least partially IFNγ-independent pro-atherogenic role of STAT4. STAT4 is expressed in T cells, but also detected in macrophages (MΦs). Stat4−/−Apoe−/−in vitro differentiated M1 or M2 MΦs had reduced cytokine production compare to Apoe−/− M1 and M2 MΦs that was accompanied by reduced induction of CD69, I-Ab, and CD86 in response to LPS stimulation. Stat4−/−Apoe−/− MΦs expressed attenuated levels of CCR2 and demonstrated reduced migration toward CCL2 in a transwell assay. Importantly, the percentage of aortic CD11b+F4/80+Ly6Chi MΦs was reduced in Stat4−/−Apoe−/− vs Apoe−/− mice. Thus, this study identifies for the first time a pro-atherogenic role of STAT4 that is at least partially independent of Th1 cell-derived IFNγ, and primarily involving the modulation of MΦ responses.